1974
DOI: 10.1111/j.1464-410x.1974.tb10177.x
|View full text |Cite
|
Sign up to set email alerts
|

A Geographical and Historical Survey of the Composition of Urinary Stones

Abstract: The problem of urolithiasis is not a simple one for many kinds of stones are known which probably require different conditions for their nucleation and growth. Calculi are found in the kidneys, ureters, bladder and urethra and for those not resulting from any anatomical abnormality, there is no proven reason why growth should occur in say the upper urinary tract as opposed to the lower. Nevertheless, the results of many epidemiological studies (see, for example, references in review articles such as Andersen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(30 citation statements)
references
References 9 publications
5
25
0
Order By: Relevance
“…Calcium oxalate stones were found to be the most frequent stones in the Sudan, as is known for other countries [4]. Therefore, our findings are in agreement with the observations of Sutor and coworkers that upper urinary tract stones in adults have the same composition in developing and in industrialized countries [5,6]. In contrast to the composition of pediatric stones in Europe, however, a lower but still considerable number of calcium oxalate stones was found in Sudanese children (60 vs. 43.7%).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Calcium oxalate stones were found to be the most frequent stones in the Sudan, as is known for other countries [4]. Therefore, our findings are in agreement with the observations of Sutor and coworkers that upper urinary tract stones in adults have the same composition in developing and in industrialized countries [5,6]. In contrast to the composition of pediatric stones in Europe, however, a lower but still considerable number of calcium oxalate stones was found in Sudanese children (60 vs. 43.7%).…”
Section: Discussionsupporting
confidence: 82%
“…Stones were analyzed in children who came from rural areas, where a low supply of milk and meat products is common. The high amount of NH 4 -urate stones in childhood found by us is in agreement with previous observations by Sutor et al [6], show-Urol Int 1998;61: [154][155][156] Balla/Salah/Khattab/Kambal/Bongartz/ Hoppe/Hesse [4] showed that Ca-phosphate (carbonate apatite) and struvite stones occurred more often in women and children than in male patients with urolithiasis. This might be due to the higher incidence or urinary tract infections in females and children.…”
Section: Discussionsupporting
confidence: 82%
“…While in London he was the second 'real founder' with his friend Alexander Marcet of the Medical and Chirurgical Society of London, was its first joint secretary and was chiefly responsible for founding the Society's library (Moore & Paget 1905). The most recent analysis of the composition of the Norwich stones has been that carried out by the late Dame Kathleen Lonsdale and her colleagues, using crystallographic methods, at University College, London (Lonsdale et al 1968) that was part of her group's study of urinary tract stones from various sources (Sutor et al 1974 (Shepherd 1965 …”
Section: East Anglian Bladder Stone'mentioning
confidence: 99%
“…These stones occur most frequently in boys in the first decade of life and they are composed mainly of calcium oxalate, or ammonium acid urate (3,4). The stones appear to be caused by malnutrition and they disappear as living standards improve, though the precise nature of the dietary defect, or defects, remains a matter of speculation (5 -7 ).…”
Section: Introductionmentioning
confidence: 99%